The amino acid permease PpAAP1 mediates arginine transport in maritime pine. - Llebrés, María Teresa; Castro-Rodríguez, Vanessa Viviana; Pascual-Moreno, María Belén; Ávila-Sáez, Concepción; Cánovas-Ramos, Francisco Miguel (Oxford University Press, 2021)
Forest trees have access to diverse nitrogenous compounds in the soil such as ammonium, nitrate and amino acids. Recent progress has been made in the identification and characterization of ammonium and nitrate transporters. However, much more limited is our current knowledge of amino acid transport systems despite their relevance to fully understanding nitrogen nutrition in trees. In the present study, we have identified 10 genes encoding putative amino acid permeases of the AAP family in maritime pine (Pinus pinaster Ait.). Four members of this family, PpAAP1, PpAAP2, PpAAP3 and PpAAP4 were phylogenetically related to AtAAP5, involved in arginine transport in Arabidopsis thaliana. One of these genes, PpAAP1, exhibited enhanced expression levels in maritime pine roots when arginine was externally supplied. PpAAP1 was functionally characterized by complementation of a yeast mutant strain defective in the transport of arginine, allowing yeast to take up [14C]-arginine with high affinity. Furthermore, PpAAP1 was able to restore the severely affected root uptake of arginine displayed by AtAAP5 T-DNA mutants. Uptake rates of 15N-labelled arginine were significantly higher in PpAAP1-overexpressing plants when compared to wild-type and AtAAP5 mutant plants. Taken together, our results indicate that PpAAP1 is a high-affinity arginine transporter in maritime pine.
https://openpolicyfinder.jisc.ac.uk/id/publication/1405
Keywords: Genética forestal; Arginina; Pino marítimo; Arginine; Transporte; Maritime pine